Pengaruh Green Accounting dan Carbon Emission Disclosure terhadap Nilai Perusahaan (Studi Empiris Perusahaan Emiten Sawit Yang Terdaftar di BEI dan Mengikuti Program Proper Periode Tahun 2020-2024) (Jurnal Manajemen Kreatif dan Inovasi, 2026)
This study aims to analyze the effect of green accounting and carbon emission disclosure on firm value in palm oil sector issuers listed on the Indonesia Stock Exchange (IDX) and participating in the PROPER program during the 2020–2024 period. Green accounting is proxied using the PROPER rating, which reflects a company's environmental management performance, while carbon emission disclosure is measured based on the level of carbon emission disclosure in the company's annual report or sustainability report. This study uses a quantitative approach with panel data regression analysis. The sampling technique used was purposive sampling, with the criteria being palm oil companies listed on the IDX, participating in PROPER, and consistently publishing annual reports throughout the study period. The data used are secondary data obtained from financial reports, sustainability reports, and official publications related to PROPER. The results are expected to show that the implementation of green accounting has a positive effect on firm value, as it reflects the company's commitment to sustainability and increases investor confidence. Furthermore, carbon emission disclosure is expected to have a positive effect on firm value, depending on market perception and the quality of environmental information disclosure. This research is expected to contribute to the development of environmental accounting literature and serve as a reference for regulators, investors, and company management in improving transparency and environmental performance to create sustainable corporate value.